2020
DOI: 10.1016/j.clnu.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Automated body composition analysis of clinically acquired computed tomography scans using neural networks

Abstract: Background & Aims-The quantity and quality of skeletal muscle and adipose tissue is an important prognostic factor for clinical outcomes across several illnesses. Clinically acquired computed tomography (CT) scans are commonly used for quantification of body composition, but manual analysis is laborious and costly. The primary aim of this study was to develop an automated body composition analysis framework using CT scans.Methods-CT scans of the 3 rd lumbar vertebrae from critically ill, liver cirrhosis, pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 47 publications
4
74
1
Order By: Relevance
“…The AI-based method for automated segmentation of SAT and muscle showed a high accuracy when compared to manual segmentations on a CT slice at the L3 level, with a Sørensen-Dice index of 0.96 and 0.94, respectively. These results are comparable to previous published data [12][13][14][15][16]. The reproducibility was, as expected, significantly better for 3D volumes compared to 2D area measurements.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The AI-based method for automated segmentation of SAT and muscle showed a high accuracy when compared to manual segmentations on a CT slice at the L3 level, with a Sørensen-Dice index of 0.96 and 0.94, respectively. These results are comparable to previous published data [12][13][14][15][16]. The reproducibility was, as expected, significantly better for 3D volumes compared to 2D area measurements.…”
Section: Discussionsupporting
confidence: 91%
“…In the field of artificial intelligence (AI), deep learning methods offer new possibilities for automated analysis of medical images. Recently AI-based methods for automated analysis of body composition on CT images have been presented [12][13][14][15][16]. These methods are, however, trained to segment muscle and fat on single CT slices and not using the whole 3D volume.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies approached the automated segmentation of muscle, VAT and SAT within the L3 vertebra region in a variety of ways, also including deep learning. These reported DSC ranged from 0.85–0.99 [ 16 , 17 , 18 , 19 , 37 ]; however, good comparisons between those studies cannot be made due to the use of similar patient cohorts in development and accuracy testing and restrictive sample sizes. These models were able to extract semantic information, overall muscle shape and adipose tissue; nevertheless, these studies analyzed computed tomography scans, which were made in a controlled (non-trauma) setting [ 16 , 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies showed improved and accurate body composition on CT [ 14 , 15 ]. For muscle mass measurement, recent studies created and validated automated segmentation of the abdominal muscle on manually extracted CT-image at the L3 level [ 16 , 17 , 18 , 19 ]. These studies, including patients with varying medical conditions, showed detailed information regarding severity of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, deep learning has been shown to be particularly well suited to segmentation tasks (14,15). Previous work has demonstrated high accuracy deep learning segmentation in skeletal muscle of diagnostic quality CT scans acquired for a range of cancer and non-cancer indications (16)(17)(18). Positron Emission Tomography PET/CT studies are standard of care in staging and surveillance for a range of cancers (19)(20)(21), and are typically whole body acquisitions therefore are well suited for measurement of L3 skeletal muscle area.…”
Section: Introductionmentioning
confidence: 99%